Pengembangan Jiwa Kewirausahaan Mahasiswa Melalui Praktik Produksi dan Usaha Jasa Ditinjau dari Perspektif Psikologi - Khairunisa, Nabila; Diani, Virza Ratna; Syahrani, Amelia Indri; Supriyadi, Tugimin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Entrepreneurial development among university students is a strategic response to labor market challenges and youth economic independence. This article examines the role of production and service business practices as learning approaches that affect students’ psychological growth from a humanistic psychology perspective. Using a literature review method, the study highlights seven key psychological aspects: self-efficacy, self-concept, self-regulation, intrinsic motivation, self-actualization, creativity and innovation, and emotional intelligence. The findings reveal that hands-on entrepreneurial experiences strengthen confidence, clarify personal identity, and enhance mental resilience. In addition to economic profit, entrepreneurship provides students a platform for self-expression and psychological growth. Therefore, integrating practice-based approaches into psychology education is highly recommended to produce graduates who are adaptive, resilient, and self-reliant.